Cloud Audit Server based verification for enhancing Information Security in cloud - Ganji, Ramanjaiah; Yalavarthi, Suresh Babu (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing enables internet based data storage, accessing, portability and processing. The flexibility cloud endows comes with a few security challenges. Though plans like "Proofs of Retrievability" and "Provable Data Possession" has been created to ascertain security they can't bolster dynamic information. By and large a significant number of the peril models accept that having a fair data owners are concentrating on the exploitative cloud authority organization. In certain scenarios the client might be untrustworthy for getting the advantages by means of pay from the supplier. This research work focuses on an open inspecting plan that endows information support and reasonable discretion in data safety issues. This paper primarily focuses on developing a signature based plan to configure reasonable discretion conventions that ensures data integrity and security. The security verification establishes that the proposed method is secure and the information flow and dispute arbitration are sensible